Radicalizing safety: A critical narrative analysis to abolish the police - Drustrup, David; Hamad ,Raneem; Kim, Jae Yung; Ali, Saba Rasheed (John Wiley and Sons Inc, 2024)
The dominant narrative in much of the world is that public safety is provided by policing,evidenced by supportive rhetoric from institutional forces including politicians,media,and large budget allocations in all levels of government. Alongside a long history of police violence,especially against Black,Brown,poor,and other marginalized people,many social movements reject the idea that policing provides safety and seek other methods for community wellness. The present study utilizes critical narrative analysis (CNA) to describe how marginalized residents of a small city in Iowa construct their understanding of personal and community safety. Their stories and the dialectic exchange during interviews illustrated several counternarratives and moments of conscientization for participants and researchers where safety was deconstructed and understood outside the power of recycled institutional narratives. Participants rejected popular notions of safety such as police,and instead embraced safety through robust relationships,community resources,and forms of self-knowledge such as mental health. We analyzed their interviews as efforts to be humanly recognized within violent white supremacist structures,and their stories help to radicalize popular messages about safety. We highlight their world-making abilities as they craft their own networks of community and safety outside of the state and police. © 2024 The Authors. Analyses of Social Issues and Public Policy published by Wiley Periodicals LLC on behalf of Society for the Psychological Study of Social Issues.
Keywords: ODS 1 - Fin de la pobreza; ODS 16 - Paz, justicia e instituciones sólidas